Clinical, electrophysiological findings and evaluation of prognosis of patients with Guillain-Barré syndrome - Kılıç, Betül; Güngör, Serdal; Özgör, Bilge (The Turkish Journal of Pediatrics, 2019)
Guillain-Barré syndrome (GBS) is an acute inflammatory polyneuropathy characterized by frequent rapid progressive, ascending, symmetric weakness and areflexia. We aimed to evaluate the etiology, clinical and electrophysiological findings with treatment and prognosis of the patients with GBS in our clinic. Patients who were diagnosed with GBS in our clinic between 2009 and 2017 were evaluated retrospectively. The study included 20 female and 25 male patients. The most frequent symptom was the absence of walking (95.5%). All of the patients had muscle weakness on examination; in addition to that hyperesthesia (31%), autonomic symptoms (13.3%), sensory loss (11.1%), ataxia (11.1%), bilateral facial nerve palsy (6.6%), oculomotor nerve palsy (2.2%), and multiple cranial nerve involvement (2.2%) were the other detected findings. Ventilation support was required in 6 cases (13.3%). Acute motor axonal neuropathy (AMAN) was found in 20 patients (44.5%), acute inflammatory demyelinating polyradiculoneuropathy (AIDP) was found in 24 patients (53.3%), and acute motor and sensory axonal neuropathy (AMSAN) was only present in 1 patient (2.2%). Intravenous immunoglobulin (IVIG) was administered to 33 of the patients (73.3%). The mean hospital stay was 8.4±3.5 (2-17 days), and the relationship between the duration of hospital stay and the treatment given was statistically significant (p = 0.001). Complete remission was observed in 37 patients (82.3%) and the remaining 5 children (11.1%) experienced incomplete recovery. Three patients (6.7%) died of treatment-resistant hypotension, arrhythmia and severe pulmonary infection. The short duration of neurological deficit following infection, clinical stage of application, need for mechanical ventilation, dysautonomia, cranial nerve involvement, and current subtype were the negative prognostic factors. Although GBS is a self-limiting disease, early diagnosis and treatment are very important to reduce hospital stay with morbidity and mortality. Patients expected to be at high risk should be monitored closely.
Keywords: Guillain-Barré syndrome; childhood; electrophysiology; intravenous immunoglobulin; prognosis